(untitled) (Bangladesh Agronomy Journal, 2021)
Continuous cultivation of highly exhaustive cropping sequence in most of the irrigated fertile lands has resulted in the decline of soil physico-chemical condition in general and particularly soil organic matter (SOM) content. The experiment was laid out inasplit- plot design with irrigation (I1: traditional irrigation i.e. continuous flooding, I2: saturated condition, I3: Alternate wetting and drying) in main plots and fertilizers treatments: T0 = Control, T1 =100% (Recommended dose of chemical fertilizer), T2 =50% RDCF + 5 ton cowdung ha- 1, T3=70% RDCF + 3 ton cowdung ha-1, T4 =50% RDCF + 5 ton compost ha-1, T5 =70% RDCF + 3 ton compost ha-1, T6 = 50% RDCF + 3.5 ton poultry manure ha-1, T7 =70% RDCF + 2.1 ton poultry manure ha-1to the sub - plots. The rice yields were not significantly affected by different irrigation but higher grain yields were obtained in continuous flooded irrigation. The treatment T7 gave higher Boro and T. Aman rice yields. The higher Boro rice grain yields were obtained from I1T7 (70% RDCF + 2.1 ton poultry manure ha-1 with continuous flooded irrigation) followed by I3T7 (alternate wetting and drying + 70% RDCF + 2.1 ton poultry manure ha-1). The 100% RDCF was applied to T. Aman rice resulted residual effects of fertilizer and the higher T. Aman rice yields were recorded in I2T2 (saturated condition + 50% RDCF + 3 ton cowdungha-1) followed by I2T3 (saturated condition + 50% RDCF + 3 ton cowdungha-1) treatment combinations due to more residual effects of inorganic plus manure application during Boro rice cropping. The highest organic matter level was found in post-harvest soils where inorganic fertilizer plus cowdung were used and soil pH increased by using poultry manure. The higher levels of available P and K concentrations were observed in the post experiment soils where fertilizer and manure were applied. Bangladesh Agron. J. 2021, 24(1): 71-81